Assessment of accumulation of tanning substances in multiple aged shrubby cinquefoil growing in the North Caucasus - M. I. Stalnaya; N. O. Sichko (Новые технологии)
The article is devoted to the biochemical study of the quantitative composition of tanning substances in the plants of multi-aged shrubby cinquefoil. Cultural populations grown in the North Caucasus (the Republic of Adygea) have been analyzed. The studies have been conducted for over six years throughout the growing period, starting from the regrowth phase, budding, flowering and ending with the late fruiting phase. To study biologically active substances a well-known and tested method for determining tanning substances in medicinal plant materials has been used - the Leventhal method modified by L.А. Kursanov - which allows determining the sum of all phenolic compounds, but the use of Neubauer's conversion factor makes it possible to determine the content of tanning substances. The considered method is quite often used in physiological and biochemical studies, including biochemical analyses in tea production. The article provides a detailed analysis of investigated aboveground organs of the Caucasian populations. It has been shown that the researched plant can be used as a plant material in food and medical industry from the age of three. Particular attention was paid to the fact that during the flowering period the content of tanning substances reached its maximum.